Analisis Hambatan Belajar Siswa Dalam Mata Pelajaran IPS Kelas VI SD Negeri Perdopo 02 Gunungwungkal - Dwi Husna Maulida; Erik Aditia Ismaya (JANACITTA, 2024)
The purpose of this research is to (1) determine descriptively the learning barriers or difficulties experienced by class VI students at SDN Perdopo 02 who study social science subjects, (2) To describe the factors that cause learning barriers experienced by students, (3) To describe Teachers' efforts to overcome student obstacles in learning social studies in class VI. This research is a qualitative research using the case study method with the object being class VI students at SD Negeri Perdopo 02 odd semester of the 2023/2024 academic year with a total of 18 students. The data collection techniques for this research are in the form of questionnaires, interviews, observations and document studies. The data analysis techniques in this research are data reduction, data presentation and verification. The results of this research can show that (1) the types of obstacles experienced by students in learning social studies, (2) the factors that cause learning difficulties for students learning social studies in class VI students at SD Negeri Perdopo 02, namely interest factors, learning motivation factors, use of models or methods. which are not appropriate, as well as a lack of inadequate facilities and infrastructure, (3) Efforts to overcome obstacles for class VI students at SD Negeri Perdopo 02 can be carried out by teachers, parents and students using identification, diagnosis and providing assistance to students. Abstrak Tujuan penelitian ini adalah untuk (1) mengetahui secara deskriptif hambatan belajar yang dialami siswa kelas VI SDN Perdopo 02 yang belajar dalam mata pelajaran ilmu pengetahuan sosial, (2) Untuk mendeskripsikan faktor penyebab hambatan belajar yang dialami siswa, (3) Untuk mendeskripsikan upaya guru dalam mengatasi hambatan siswa dalam pembelajaran IPS kelas VI. Penelitian ini merupakan penelitian kualitatif menggunakan metode studi kasus dengan objek siswa kelas VI SD Negeri Perdopo 02 semester ganjil tahun ajaran 2023/2024 dengan jumlah 18 siswa. Teknik pengumpulan data penelitian ini berupa angket, wawancara, observasi dan studi dokume. Teknik analisis data pada penelitian ini yaitu reduksi data, penyajian data dan verifikasi. Hasil dari penelitian ini dapat menunjukan bahwa (1) jenis hambatan yang dialami siswa dalam pembelajaran IPS, (2) faktor peyebab terjadinya kesulitan belajar siswa belajar IPS pada siswa kelas VI SD Negeri Perdopo 02 yaitu faktor minat, faktor motivasi belajar, penggunaan model atau metode yang belum tepat, serta kurangnya sarana dan prasarana yang belum memadai, (3) upaya mengatasi hambatan siswa kelas VI SD Negeri Perdopo 02 dapat dilakukan oleh guru, orang tua, dan siswa menggunakan langkah identifikasi, diagnosis, dan memberikan bantuan kepada siswa.